Bio-regenerative Life Support Systems for human space exploration - Zabel, Paul (2018)
This presentation explains the functionality and importance of bio-regenerative life Support Systems for future human spaceflight. The Focus is here on space greenhouse Systems and plant cultivation in space. The presentation also Shows the current Status of the EDEN ISS greenhouse in Antarctica and explains the Research conducted in the facility in 2018.